HUBUNGAN MOBILISASI DINI DENGAN LAMANYA PENYEMBUHAN LUKA PADA PASIEN PASCA OPERASI APENDIKTOMI DI RUMAH SAKIT GRANDMED LUBUK PAKAM - Arfah May Syara; Anita Srigandaria Purba; Kuat Sitepu; Tiurma Siringo-ringo; Afeus Halawa; Samuel Panjaitan (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2021)
One of the recovery processes for postoperative appendectomy patients can be attempted by planning and implementing early mobilization, namely the steps that are carried out immediately on postoperative patients starting from lifting the upper and lower extremities and doing right and left tilts, and sitting on the side of the bed until the patient get out of bed, stand up and begin to learn to walk with assistance according to the patient's condition. This study aims to determine the relationship between early mobilization and the duration of wound healing after appendectomy surgery at Grandmed Lubuk Pakam Hospital. This research is a quantitative research with a cross sectional design. The research population is the entire object of research or the object under study. The population in this study were all post-op appendectomy patients who were being treated at the GrandMed Lubuk Pakam Hospital in 2021 as many as 63 people. The sampling technique used is purposive sampling with a sample of 15 people. Data analysis was performed by univariate, bivariate with Chi-square test at 95% confidence level. The results of this study were 11 respondents (73.3%) with good wound healing, 10 (66.7%) who did not mobilize well, and 10 respondents (66.7%) who did not mobilize well. 4 people (26,7) with moderate wound healing as many as 5 people (33,3%). The results of data analysis showed that there was a relationship between early mobilization and the duration of wound healing in appendectomy patients at Grandmed Lubuk Pakam Hospital in 2021 with p value = 0.001. Respondents who have an early mobilization rate are likely to have faster wound healing. It is recommended to post-op appendictomy patients to mobilize early for better wound healing.